Shear resistant capacity of steel fibres reinforced concrete deep beams: An experimental investigation and a new prediction model. (October 2021) - Dang, Tung D.; Tran, Duong T.; Nguyen-Minh, Long; Nassif, Ayman Y.
Abstract: The research efforts reported here are aimed at experimentally investigating the effects of incorporating steel fibres, with various dosages, on the shear capacity and shear behaviour characteristics of reinforced concrete deep beams. The primary experimental results obtained during this research, as well as an extensive secondary dataset, were used to examine and verify a proposed new model by the authors for calculating the shear resistance of steel fibres reinforced concrete (SFRC) deep beams. The experimental investigation involved 12 deep beams with four fibres dosages, namely: 0, 30, 40, and 65 kg/m 3 and three stirrup ratios, namely: 0.1%, 0.15%, and 0.25%. The experimental results have shown that steel fibres improved the shear resistance of the deep beams (up to 55%), decreased the shear crack width (up to 68%), reduced the displacement of the beams (up to 57%), and enhanced the deformation capacity of the beams (up to 45%). The authors propose a new semi-empirical formula for estimation of the shear resistance of SFRC deep beams. The accuracy of the formula was evaluated using 116 beams dataset including a primary dataset obtained during this project as well as the published secondary dataset. The reliability and accuracy of the proposed formula were compared with other four published formulas. It is evident that the newly proposed formula increases the accuracy and reliability of the estimation of the shear resistance of SFRC deep beams when compared to the previously published models.